MAKNA SELF-ACCEPTANCE DALAM ISLAM (ANALISIS FENOMENOLOGI SOSOK IBU DALAM KEMISKINAN DI PROVINSI D.I YOGYAKARTA) - Reza Mina Pahlewi (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2019)
AbstractThis study aims to uncover the meaning of Self-Acceptance of mothers who live below the poverty line. With informants 10 mothers living below the poverty line in the province of D.I Yogyakarta, this study is a qualitative-phenomenological. Data was collected through FGD and interviews and analyzed inductively. The results showed that mothers living below the poverty line in the province of D.I Yogyakarta had different definitions of Self-Acceptance. Even so, they have a common concept in accepting the life they have to live in, that is patience. Patience is part of Self-Acceptance and at this point, there is a common perception in living life below the poverty line. Keywords: self-acceptance, phenomenological analysis, mothers, poverty.